Formation of the visual image of the city (Kharkiv) Under wartime conditions (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
The study addresses the issue of a comprehensive and systematic approach to theformation and restoration of the visual image of post-war cities in Ukraine. It emphasizes that thisprocess extends far beyond architectural and construction tasks, functioning instead as a strategic,multi-layered project of socio-psychological rehabilitation, cultural identification, and informationalresilience. The visual environment of a post-war city is interpreted as an active communicativemedium that influences collective memory, emotional well-being, and social cohesion, particularlyin societies affected by prolonged military conflict.Special attention is paid to participatory practices as a key foundation for legitimacy,inclusivity, and trust in post-war urban transformation. The research examines contemporarymethods of active public engagement, including co-design processes, community-based decisionmaking,and the application of innovative digital tools such as virtual reality (VR). VR technologiesare analyzed as instruments for project visualization, inclusivity testing, risk mitigation, and theachievement of social consensus prior to implementation, thereby democratizing the design processand reducing conflict between stakeholders.The paper proposes a comprehensive, multi-phase program that integrates long-term strategicplanning instruments, such as the development of urban master plans, municipal design codes, andvisual regulation frameworks, with tactical and operational solutions. These include localizeddesign interventions in specific urban areas (streets, squares, small public spaces, courtyards), rapidurban improvement measures, and the creation of exemplary “postcard” views and selfie zones.Such interventions are considered not merely as aesthetic enhancements, but as tools for shaping apositive visual narrative, strengthening urban branding, and supporting psychological recoveryduring and after the conflict.Using Kharkiv as a case study, the research analyzes practical strategies for maintaining andpreserving a positive visual image of the city under conditions of active hostilities. These strategiesinclude the organization of safe festive, cultural, and memorial events, as well as temporary andadaptive spatial interventions, which function as mechanisms for sustaining community morale,reinforcing collective identity, and counteracting narratives of destruction.The study concludes that post-war recovery presents a unique opportunity not only to rebuilddamaged infrastructure, but to achieve a qualitative transformation of the urban environment. Thistransformation aims to produce cities that are more humane, resilient, visually coherent, andsocially inclusive, grounded in European values, cultural continuity, and active civic participation.The findings contribute to the interdisciplinary discourse on post-conflict urbanism and may serveas a methodological framework for policymakers, urban planners, architects, and local communitiesinvolved in the reconstruction of war-affected cities.
Keywords: visual image of the city; architectural environment; participatory practices; memorialization; social cohesion; psychological well-being; post-war recovery